A mesoporous cationic metal–organic framework with a high density of positive charge for enhanced removal of dichromate from water. Issue 20 (3rd May 2019) - Zou, Yu-Huang; Liang, Jun; He, Chang; Huang, Yuan-Biao; Cao, Rong
Abstract : A mesoporous cationic metal–organic framework (FJI-C11) was firstly employed to capture efficiently dichromate ions from water. Abstract : An imidazolium-functionalized mesoporous cationic Cr-based metal–organic framework (MOF) with high densities of positive charges was synthesized for the first time via a mixed-solvent strategy. The cationic mesoporous Cr-based MOF showed excellent adsorption performances in the removal of dichromate Cr2 O7 2− from water with a large uptake of 321 mg g −1 and good regeneration ability.